CONTESTED SPACE IN COASTAL CITY. A Case of Conservation, Community and Tourism Development in Manado – Indonesia - Reni Syafriny; Sangkertadi Sangkertadi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2019)
The growth of coastal cities has experienced a shift and brings changes in the space value in coastal areas of production to the consumption. Capitalist mode of production spread evenly in areas previously held by various traditional modes of economic and social exchange. The role of the tourism and development market strongly determined the changes that often lead to contradictions and conflicts of spatial function. This paper explores the reasons of spatial competition and possibility to make more just spaces on the coast by seeking spatial balance between traditional and modern one, capital space and indigenous as well. Using a multilayered approach in the case study research, this paper revealed the phenomenon of contested space, particularly on the power relation framework on the specific sites using by different groups of interests: Littoral fishermen, recreation and tourism, and private company. Paper attracts attention to the capitalist policies that is the main reason of spatial tension that produced domination and resistance on the modern coastal space. Architects and urban planners should routinely assess the spatial equity of public resources such as coastal resources because understanding the vagaries of public resource distribution can help to facilitate provision of the public good and ultimately social justice.